2020
DOI: 10.1257/app.20180201
|View full text |Cite
|
Sign up to set email alerts
|

Gender Homophily in Referral Networks: Consequences for the Medicare Physician Earnings Gap

Abstract: I assess the extent to which the gender gap in physician earnings may be driven by physicians’ preference for referring to specialists of the same gender. Analyzing administrative data on 100 million Medicare patient referrals, I provide robust evidence that doctors refer more to specialists of their own gender. I show that biased referrals are predominantly driven by physicians’ decisions rather than by endogenous sorting of physicians or patients. Because most referring doctors are male, the net impact of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 45 publications
1
43
0
Order By: Relevance
“…Further, administrative data from the broader setting beyond the randomized evaluations allow us to provide context to our estimates and conduct policy counterfactuals evaluating the effects of diversifying the doctor workforce. Our evidence on gender homophily in patient selections of providers in broader settings complements prior work illustrating gender homophily in patient selections of urologists (McDevitt and Roberts, 2014) and in referrals among doctors (Zeltzer, 2020).…”
Section: Related Literaturesupporting
confidence: 66%
“…Further, administrative data from the broader setting beyond the randomized evaluations allow us to provide context to our estimates and conduct policy counterfactuals evaluating the effects of diversifying the doctor workforce. Our evidence on gender homophily in patient selections of providers in broader settings complements prior work illustrating gender homophily in patient selections of urologists (McDevitt and Roberts, 2014) and in referrals among doctors (Zeltzer, 2020).…”
Section: Related Literaturesupporting
confidence: 66%
“…Existing works have shown that the gender wage gap tends to grow over time, arguably due to child-bearing and family obligations which lead women to decrease their worked hours (see Zeltzer, 2020, for a study of physicians). Unlike other jobs, teaching has fairly standard hours and is thought to be a "family friendly" occupation since its work hours coincide with children's school hours.…”
Section: Differences By Age and Senioritymentioning
confidence: 99%
“…One finding suggests that the decision to refer a patient is largely driven by gender, and that there may a preference for a male physician when males make the referral due to homophily, the same driver of our patient-sharing outcome. 24 This dynamic warrants further research on dyad gender dynamics and how they can be managed effectively to improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals tend to form social ties with people similar to themselves, especially along dimensions of race, gender, and education. 23 , 24 We are interested in provider–provider homophily because it increases the likelihood of ties (referrals) between two individuals. Homophily can also contribute to the likelihood of reciprocity and support between actors (providers).…”
Section: Introductionmentioning
confidence: 99%